Auditoría financiera y su incidencia en el resultado económico de la empresa "Comercial Litardo" cantón Quevedo año 2014 - Cherres Chuquicondor, Ibeth Jessenia (2016)
This research project was conducted in the company "Commercial Litardo" located on Seventh Street intersection Bolivar No. 118 in Canton Quevedo, Los Rios province; in order to determine the impact of the financial audit in economic performance, for which it was necessary to analyze policies and rules governing the company to identify the compliance of the law, and evaluate internal control and measure the degree reasonableness of financial information to issue the respective audit report for the period 2014; Three types of research were applied: applied, descriptive and historical that were used within the company premises with due assistance from owner manager commercial, methods of logical research deductive and analytical who helped in the compilation of information used concerning the proposed theme for the audit process COSO I which yielded acceptable results having a confidence level of 85%, a risk level of 15% and audit risk is 0.60% was used. Respetivamente applied analysis of indicators measuring solvency allowed value $ 3.57 for every dollar invested by borrowing capacity and 43.57% indicating that the trade is financed by equity and gross margin after deducting cost of sales is 0.44% and a net margin of 22.08% profit for the company at the end of the closing cycle of fiscal 2014. The investigation concluded that the analysis applied to the Annual Operating Plan Survey revealed inadequate implementation procedures which in turn allow improper administration and avoid future problems